Pengembangan Media Pembelajaran Berbantuan Aurora 3d Presentation Pada Mata Pelajaran Administrasi Umum Kelas X OTP Di SMK Negeri 1 Jombang - Syehifan Praha Sadani; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
Aurora 3D Presentation is a software to create 3D presentation slides that can process slides by producing various images, text and video models in 3-dimensional form. Based on these, this study aims to (1) Describe the results of the development process of learning media, (2) Analyze and find out the feasibility of learning media and (3) Analyze student responses to Aurora 3D Presentation-assisted learning media in general administration subjects in class X OTP at SMK Negeri 1 Jombang. In this study, researchers used the 4D media development model. Where the 4D stage consists of define, design, develop, and disseminate. Based on the results of the validation of Aurora 3D Presentation media development on the validation of the material obtained results of 95.67% with "very strong" indicator statement, while the validation of the media obtained a result of 96% with "very strong" indicator statement. Then there are average results from both aspects of 95.83%. Although there are limitations at the dissemination stage and are limited to limited trials, students' responses to Aurora 3D Presentation-based learning media conducted on 20 students get 96.33% with "very strong" indicator statement. From these results, it is known that the development of instructional media assisted by Aurora 3D Presentation was declared "very feasible".